Assessing soil bacterial community and dynamics by integrated high-throughput absolute abundance quantification - Lou, Jun; Yang, Li; Wang, Haizhen; Wu, Laosheng; Xu, Jianming (PeerJ, 2018)
Microbial ecological studies have been remarkably promoted by the high-throughput sequencing approach with explosive information of taxonomy and relative abundance. However, relative abundance does not reflect the quantity of the microbial community and the inter-sample differences among taxa. In this study, we refined and applied an integrated high-throughput absolute abundance quantification (iHAAQ) method to better characterize soil quantitative bacterial community through combining the relative abundance (by high-throughput sequencing) and total bacterial quantities (by quantitative PCR). The proposed iHAAQ method was validated by an internal reference strain EDL933 and a laboratory strain WG5. Application of the iHAAQ method to a soil phenanthrene biodegradation study showed that for some bacterial taxa, the changes of relative and absolute abundances were coincident, while for others the changes were opposite. With the addition of a microbial activity inhibitor (NaN3), the absolute abundances of soil bacterial taxa, including several dominant genera of Bacillus, Flavobacterium, and Paenibacillus, decreased significantly, but their relative abundances increased after 28 days of incubation. We conclude that the iHAAQ method can offer more comprehensive information to reflect the dynamics of soil bacterial community with both relative and absolute abundances than the relative abundance from high-throughput sequencing alone.
Keywords: Quantitative bacterial ecology; Absolute abundance; iHAAQ; High-throughput sequencing; qPCR; Soil